Hubungan motivasi kerja dengan kinerja karyawan di ruang operasi dan pemeliharaan (op) - Hertanto, Ridho Bagas; Rukmana, Nova Mega; Novariana, Nana (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: There has been a decline in the effectiveness of public services in the irrigation sector, characterized by delayed technical responses and suboptimal irrigation canal maintenance. The actual situation indicates a decline in employee performance triggered by a lack of motivation, incentives, training, and weak supervision. Purpose: To analyze the relationship between work motivation and employee performance at the Adipuro Irrigation Regional Technical Implementation Unit (UPTD), Central Lampung Regency. Method: A quantitative approach with a cross-sectional design. The population and sample were all 30 employees in the Operations and Maintenance (OP) division at the Adipuro Irrigation UPTD. Data were collected through questionnaires and analyzed using descriptive and inferential statistics, with the Chi-Square Test as the primary method for testing hypotheses. Results: The majority of respondents (60% or 18 people) reported a